K-wire Fixation of Closed Hand Fractures Outside the Main Operating Room Does Not Increase Infections. Issue 11 (21st November 2022) - Gillis, Joshua A.; Lalonde, Jan; Alagar, David; ,; Azzi, Alain; Lalonde, Donald H.
Abstract : Background: Closed reduction and internal fixation (CRIF) of closed hand fractures in the main operating room (OR) is much more expensive than outside of the OR. However, there is a reluctance to fix fractures out of the OR due to the perceived increase in infections. Our goal was to prospectively analyze the infection rates of performing CRIF of closed metacarpal and phalangeal fractures in these two settings. Methods: A multicenter prospective analysis of patients undergoing CRIF of metacarpal or phalangeal fractures inside or outside the OR was performed. Demographic data, injury characteristics, surgery information and postoperative infectious complications were recorded, including cellulitis, frank pus, and osteomyelitis. Results: The study involved 1042 patients with a total of 2265 Kirschner-wires (K-wires). Infection rates were not statistically higher in the 719 patients who had CRIF outside of the OR (cellulitis 2.5%, frank pus 1.4%) compared with the 323 patients with CRIF in the OR group (cellulitis 3.4%, frank pus 2.5%). The OR group had a longer time to operation and a longer procedure time, but a shorter time with the K-wires in place. Conclusion: K-wire fixation of closed hand fractures outside of the OR under field sterility is safe because it does not increase infectious complications compared to CRIF in the main OR under full sterility.